A low power switched-capacitor interface for resistive bridge sensors - Li, Yue (2016)
A low-power low-offset switched-capacitor interface for resistive bridge sensor designed in UMC 65nm technology is presented. It converts the resistance imbalance of the bridge sensor into a saw tooth frequency using current-mode sensing. The half-bridge sensor interface and quarter-bridge sensor interface are configured to validate the circuit. The sensor interface consumes 337 μW at a 1.2 V single supply and display excellent energy-noise FOM. This is considered as a low-voltage low-energy design with respect to other reported counterparts.